VEGF in tumor progression and targeted therapy - Chekhonin, Vladimir P; Shein, Sergey A; Korchagina, Anna A; Gurina, Olga I (Current cancer drug targets, 2013)
Progression of solid tumors depends on vascularization and angiogenesis in a malignant tissue. Among a whole range of proangiogenic factors, a vascular endothelial growth factor A (VEGF-A) plays a key role. Blockade of VEGF may lead to regression of vascular network and inhibition of a tumor growth. In the present time, bevacizumab has been introduced into wide clinical practice in therapy of breast cancer, colorectal cancer and recurrent high-grade gliomas (HGGs). Coadministration of antiangiogenic therapy with irinotecan may increase probability of the response to the treatment and prolong progression-free survival rate (PFS). Moreover, bevacizumab is well tolerated and significantly improves patient's quality of life. However, in the case of brain tumors, the efficiency of such an approach is controversial. The antiangiogenic therapy can slightly delay tumor growth and does not lead to complete recovery. In addition, it contributes to enhanced tumor cell invasion into the normal brain. The mechanisms of resistance include activation of alternative proangiogenic signaling pathways, of an invasive population of tumor cells, metabolic change toward glycolysis and recruitment of myeloid bone marrow-derived cells to tumors. Obviously, that anti-VEGF therapy as monotherapy was not effective against HGGs. To enhance the antitumor treatment efficacy, it is necessary to develop a multi-target strategy to inhibit critical processes in malignancy progression such as angiogenesis, invasion, autophagy, metastatic spread, recruitment of bone marrow-derived endothelial cells and tumor stem-like cells. In addition, anti-VEGF antibodies have shown a promising result as a tumor-targeting vector for delivery therapeutic and diagnostic drugs in brain tumors.